Site selection of equipment and military equipment based on natural factors Case Study: Oman Sea Shores - mohamda poodineh; morteza esmailnejad; sohrab qaedi; Mohammad Ali Shirazi kharazi (تحقیقات کاربردی علوم جغرافیایی)
The coastal are geographically diverse from important areas for attracting populations and economic activities, especially military ones. Understanding the natural environment's behavior on the coast can help plan and deploy military activities. Therefore, this study evaluates the role of natural factors (climate and geomorphology). For this purpose, the most important variables affecting the location of military activities are selected, and then the data of the weather stations of the region for a period of 30 years to create climate databases and layers of features of the earth's surface including slope, tilt, topography, etc., for The formation of natural databases was selected and organized in the GIS environment. Then, using decision-making methods (AHP, ANP), we evaluated the impact criteria in the locational process. Ultimately, using the Fuzzy Collaborative Model, the final map provided the best places to deploy military equipment and equipment on the coast of the Oman Sea. The results showed that more suitable locations are located in the eastern coastal strip and some western locations. However, scattered locations with the least vulnerability and non-operational basics can be found in the coastal areas in the final map.